Fine-Scale Foraging Behavior of Humpback Whales (Megaptera novaeangliae) in Southeast Alaska - Burrows, Julia A. (2017)
Humpback whales (Megaptera novaeangliae) are one of the biggest animals on the planet and thus require large quantities of dense prey to meet their energetic requirements. They feed using discrete lunges and filtration to capture their euphausiid (krill) and schooling fish prey. They forage independently, in small groups, or in larger coordinated groups of up to 15 or more individuals. This dissertation aims to improve our understanding of the fine-scale foraging behavior of humpback whales in Southeast Alaska. High-resolution biologging tags (DTAGs) were deployed and focal follows were conducted on foraging humpback whales in Sitka Sound, Alaska in September 2012 and Tenakee Inlet, Alaska in April 2013. Concurrently, prey around tagged foraging whales was sampled using a Simrad EK 60 scientific echosounder, and acoustic data were ground-truthed with net tows for krill and hook and line samples for fish. Whale and prey data were then spatially and temporally integrated to determine characteristics of prey patches upon which whales fed. Results indicate that humpbacks targeted the densest layer of krill in Sitka Sound, maximizing their energetic gain by capturing the most prey with each lunge. When foraging together in groups, bubble-net feeding humpback whales repeated specific behaviors within a foraging bout, suggesting that whales were feeding cooperatively using role specialization and a division of labor to improve foraging efficiency. Finally, the group size of humpbacks increased throughout a week-long study as whales exploited a pre-spawning Pacific herring (Clupea pallasii) aggregation in Tenakee Inlet, which responded to the increased predation pressure with changes in school behavior. As the population of North Pacific humpback whales increases and global warming continues to affect marine ecosystems, a better understanding of predator-prey interactions is crucial to best conserve and manage humpback whales and their ecosystem as a whole.